Beautiful Nightmares: Low Self-Esteem Causes and Effects to Lara and Ayunindya’s Life - Jessica Azalea Hendrike (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
My screenplay Beautiful Nightmares is the story of Lara, a singer and Ayunindya, the assistant manager who both struggling with their self-esteem. Using crime as the genre of my story and Film Noir as the subgenre, I look into the worst nightmare of two persons with low self-esteem can bring to someone else.  The main idea of my creative writing focuses on the causes and effects of low self-esteem, I also deal with the roles of family and friends in influencing someone value of him or herself. However I believe low self-esteem can cause a big nuisance, especially when it comes to anxiety, obsession, violence and ended up with criminal behavior. To help me creating this screenplay, I use the theory of The Looking Glass Self by Charles Horton Cooley, theory of Self-Esteem and Adolescent by Morris Rosenberg, the theory of possession by L. Firestone, and Rosenbaum and DeCharms’ theory of criminal behavior on someone with a low self-esteem. Later in the story it reveals how Lara and Ayunindya’s self-esteem are influenced by their family and friends. Furthermore, they ended up committing murder.Keyword: Low Self-Esteem, Possession, Criminal behavior.